Double dose efficiency of the yellow rust resistance gene Yr17 in bread wheat lines. (25th October 2019) - Coriton, Olivier; Jahier, Joseph; Leconte, Marc; Huteau, Virginie; Trotoux, Gwenn; Dedryver, Françoise; de‐Vallavieille‐Pope, Claude
Abstract: Yellow rust, caused by Puccinia striiformis f. sp. tritici, is one of the most severe wheat disease worldwide. Crop losses have ranged from 10% to 70% and up to 100% in extreme conditions. Eighty‐two resistance genes, designated Yr, have been identified. Among them, Yr17 derived from Aegilops ventricosa and located on chromosome 2A has been widely used in wheat breeding. However, it had been overcome already. Through recombination of the Ae. ventricosa Yr17 ‐carrying 6N v chromosome with 2D of wheat, we introduced Yr17 onto chromosome 2D. Then, lines carrying Yr17 on both 2A and 2D were generated. Seedlings of the latter, as well as those carrying a single dose of Yr17 either on 2A or on 2D, were inoculated with virulent or avirulent strains on wheat seedlings. The different genotypes were fully susceptible for the two pathotypes that are virulent on Yr17 . In the case of avirulent pathotypes, the Yr17 double dose lines were fully resistant, while those with the Yr17 gene only on either 2A or 2D had intermediate resistance reactions towards one or the other or both pathotypes.